Alkyl side-chain and fluorination engineering in the indeno[1, 2-b]fluorene-based small-molecule acceptors for efficient non-fullerene organic solar cells. (January 2019) - Lin, Zhijing; Huang, Kunxiang; Wang, Zhaolong; Chen, Xianjie; Sun, Jing; Xu, Zheng; He, Tian; Yin, Shouchun; Li, Miaomiao; Zhang, Qian; Qiu, Huayu
Abstract: A series of non-fullerene acceptors based on the indeno[1, 2- b ]fluorene central moiety, with thiophene or 3-octylthiophene as π-bridge and either non-fluorinated or fluorinated 2-(3-oxo-2, 3-dihydro-1 H -inden-1-ylidene) malononitrile as end-capping groups (namely ICBF-O, ICBF, FICBF-O and FICBF), have been designed and synthesized. The effect of alkylation of the π-bridge and fluorination of the end-capping groups on the absorption spectra, energy levels, active layer morphology and photovoltaic performance were systematically investigated. Alkylation upshifts the molecular LUMO levels and thereby a high open circuit voltage ( V oc ) of 1.06 V was obtained. However, the larger band gap induced by alkylation led to lower short circuit current ( J sc ). Fluorinated acceptors display lower V oc but higher J sc and FF compared with non-fluorinated acceptors, coinciding with their lower LUMO levels, narrower band gaps and favourable morphology. As a result, the non-fullerene solar cells (NFSCs) based on FICBF showed the highest PCE of 7.41% among these four acceptors. The ICBF based device delivered a comparatively high V oc of 0.99 V and a PCE of 6.07%. The results demonstrated that indeno[1, 2- b ]fluorene is a promising building block for efficient NFSCs. Graphical abstract: Four new small-molecule acceptors based on indeno[1, 2- b ]fluorene were designed and synthesized. The impact of alkyl chain of the thiophene spacer and fluorination of end-capping groups on the molecular band gaps, energy levels and photovoltaic performance was systematically investigated. Image 1 Highlights: Four new small-molecule acceptors based on indeno[1, 2- b ]fluorene were synthesized. The impact of alkyl chain and fluorination on molecular properties was systematically investigated. Non-fullerene solar cells based on FICBF showed the highest efficiency of 7.41%.